ANALYSIS OF HOUSEHOLD CONSUMER PREFERENCES FOR TEA PRODUCTS IN BANJARMASIN CITY, SOUTH KALIMANTAN PROVINCE - Fuzi Maulana Ash’ari; Yarna Hasiani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Tea is a beverage made from the processed leaves of Camellia sinensis. It is one of the most widely consumed beverages in the world, including in Indonesia. Thus, it is essential to examine household consumer preferences in determining tea purchases in Banjarmasin City. This study aims to analyze household consumer preferences for tea products in Banjarmasin City. Based on conjoint analysis, the attributes considered by consumers according to the utility estimate values indicate that household consumer preferences for tea products are box packaging, tea bags, and green tea with jasmine aroma. According to the importance values, aroma is the most important attribute with a value of 44.708, followed by type of tea 26.894, packaging 16.606, and form 11.792.